2011
DOI: 10.1155/2011/167898
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in Patients with Acute Stroke

Abstract: Stroke is a devastating event that carries a potential for long-term disability. Malnutrition is frequently observed in patients with stroke, and dysphagia contributes to malnutrition risk. During both the acute phase of stroke and rehabilitation, specific nutritional interventions in the context of a multidisciplinary team effort can enhance the recovery of neurocognitive function. Early identification and management of malnutrition with dietary modifications or specific therapeutic strategies to ensure adequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 42 publications
3
56
0
9
Order By: Relevance
“…Dysphagia has been associated with increased mortality and morbidity (1). In addition, dysphagia is a major risk factor for malnutrition, and in turn, delays patient recovery from illness (2,3). These studies as well as our study suggest importance of feeding enough nutrients in acute care hospitals in order to avoid malnourishment.…”
Section: Discussionsupporting
confidence: 66%
“…Dysphagia has been associated with increased mortality and morbidity (1). In addition, dysphagia is a major risk factor for malnutrition, and in turn, delays patient recovery from illness (2,3). These studies as well as our study suggest importance of feeding enough nutrients in acute care hospitals in order to avoid malnourishment.…”
Section: Discussionsupporting
confidence: 66%
“…Following a stroke, patients experience a range of physical, cognitive and emotional problems, including mobility and balance impairment, pain, vision impairment, tiredness and fatigue, dysarthria, dysphagia, memory impairment, depression, anxiety and behavioural changes 79 80. Patients with stroke who lose the ability to maintain a safe and adequate oral intake are at increased risk of nutritional decline, which is associated with increased mortality, longer hospitalisation, higher rates of pressure ulcers and increased rates of urinary and respiratory tract infections 1. Enteral feeding is commonly used in patients following a stroke in order to establish an alternative route of nutrition, hydration and medication.…”
Section: Enteral Feeding In Strokementioning
confidence: 99%
“…Malnutrition is a very common problem in patients with neurological disorders, such as stroke,1 motor neurone disease,2 Parkinson's disease,3 Alzheimer's disease and other dementias 4. The cause of malnutrition in these patient groups is multifactorial, including suboptimal dietary intake (because of dysphagia, lack of appetite, reduced mobility, requirement for an unpalatable diet, reliance on others and physical difficulties in preparing and consuming food); increased metabolism; physical exertion and other comorbidities affecting metabolic status 5 6.…”
Section: Introductionmentioning
confidence: 99%
“…Intake in this study was similar to that described by Foley et al and Nip et al, however, exceeded that described by Gariballa et al Foley et al concluded that their population of stroke patients demonstrated adequate nutritional intake; while Nip et al reported adequate protein intake and calorie intake that-while less than ideal-was not inadequate to meet daily energy requirements in their population (N. Foley et al, 2006;Nip et al, 2011). As it has been reported that that preexisting malnutrition can increase the risk for worsening nutritional status and old age can contribute to poor nutritional status in the stroke population, (Bouziana & Tziomalos, 2011) the fact that Gariballa et al studied only malnourished patients who were much older than patients in the other studies explains the poorer intake in their population (Gariballa et al mean age 80 ± 7 years;Foley et al 69 ± 11.3;Nip et al 69 ± 15,here 59.9 ± 16.3) (N. Foley et al, 2006;S.E. Gariballa et al, 1998b;Nip et al, 2011).…”
Section: Discussionmentioning
confidence: 99%